Pour une gestion améliorée des ressources humaines dans les départements universitaires—Les possibilités offertes par la modulation des tâches des professeurs - Desrosiers, Jean-Yves (Canadian Journal of Higher Education, 1991)
The management of human resources in university departments has become a central theme of discussions within the context of the financial constraints with which Canadian universities are being confronted at this time. In the Province of Quebec, task modulation is being more closely examined as a potential solution for both the improved utilization of human resources and a greater flexibility within departments. Task modulation is, however, a relatively new concept. In this paper, the Quebec literature is surveyed, a definition is proposed for the concept, and prerequisite and other conditions critical to successful implementation are described. At the same time, it is clearly indicated that task modulation constitutes only one of the many facets in the management of human resources in a university.